PENGARUH FAKTOR GEOMETRIK SUMUR RESAPAN TERHADAP PERENCANAAN DIMENSI SUMUR RESAPAN DAN PENGURANGAN LIMPASAN PERMUKAAN - Sri Amini Yuni Astuti (TEKNISIA, 2021)
To solve the problem of flooding, and to conserve groundwater, many infiltration wells have been built. To plan the dimensions and number of infiltration wells, that is influenced by the geometric factor of an infiltration well. Therefore, this paper will discuss the influence of infiltration well geometric factor on the dimensional planning and the number of infiltration wells needed, as well as those that are feasible to build based on existing land limitations. The planning of infiltration wells uses the Sunjoto method. The study location is on the UII integrated campus. Rainfall data were taken from Prumpung station in 1998 - 2016. The larger the infiltration well geometric factor, the smaller the number and dimensions of infiltration wells. For example, in the D3 Ekonomi complex, for a type of infiltration well with a diameter of 1,5 m and a height of 4 m, with , 8 units are needed, while an infiltration well with  requires 7 units. Likewise for other complexes. With the limited land available, the greater the infiltration well geometric factor used, the reduction in surface runoff is not much change, almost the same, namely 59,73 % with  and 59,79 % with F=7,4022 m.